Hormesis effects of silver nanoparticles at non-cytotoxic doses to human hepatoma cells. - Zhi-Hao Jiao; Ming Li; Yi-Xing Feng; Jia-Chen Shi; Jing Zhang; Bing Shao (PLoS ONE, 2014)
Silver nanoparticles (AgNPs) have attracted considerable attentions due to their unique properties and diverse applications. Although it has been reported that AgNPs have acute toxic effects on a variety of cultured mammalian cells and animal models, few studies have been conducted to evaluate the associated risk of AgNPs to human health at non-cytotoxic doses. In this paper, HepG2 cells were exposed to 10 nm and 100 nm AgNPs under non-cytotoxic conditions, and cell viability was assessed. At low doses, AgNPs displayed "hormesis" effects by accelerating cell proliferation. Further studies indicated that the activation states of MAPKs were differentially regulated in this process. Specifically, by increasing the expression of downstream genes, p38 MAPK played a central role in non-cytotoxic AgNP-induced hormesis. Moreover, the treatment of HepG2 cells with silver ions (Ag+) at the same dose levels induced distinct biological effects, suggesting that different intrinsic properties exist for AgNPs and Ag+.